ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) CRITERIA IN SHARIA-COMPLIANT STOCK SCREENING: A COMPARATIVE STUDY OF GLOBAL ISLAMIC INDICES - Daniyar Satybaldy; Azamat Nazarov; Henrik Johansen; Aryo Prakoso (Yayasan Adra Karima Hubbi, 2025)
The convergence of Islamic finance and sustainable investing presents a significant area of interest, driven by shared ethical principles. However, the extent to which Environmental, Social, and Governance (ESG) criteria are formally integrated into sharia-compliant stock screening remains unclear across global indices. This study aims to comparatively analyze the methodologies of leading global Islamic stock indices to determine the scope and nature of ESG integration within their sharia screening frameworks. A qualitative comparative analysis was conducted on the methodology documents of major indices, including MSCI, FTSE, S&P, and Dow Jones Islamic Markets. The findings reveal significant heterogeneity. While all indices inherently cover certain social and governance aspects through traditional sharia screening (e.g., excluding sin stocks, debt limits), explicit and comprehensive ESG frameworks are not uniformly applied. Environmental criteria, in particular, are often not systematically integrated. The study concludes that while a natural alignment between sharia principles and ESG values exists, the formal integration of ESG criteria into global Islamic indices is still nascent and inconsistent. This highlights an opportunity to develop a more holistic screening framework that explicitly combines both ethical paradigms, enhancing the appeal of Islamic finance to sustainable investors.